2023
DOI: 10.1038/s41563-023-01738-3
|View full text |Cite
|
Sign up to set email alerts
|

Precise control over gas-transporting channels in zeolitic imidazolate framework glasses

Oksana Smirnova,
Seungtaik Hwang,
Roman Sajzew
et al.

Abstract: Porous metal–organic frameworks have emerged to resolve important challenges of our modern society, such as CO2 sequestration. Zeolitic imidazolate frameworks (ZIFs) can undergo a glass transition to form ZIF glasses; they combine the liquid handling of classical glasses with the tremendous potential for gas separation applications of ZIFs. Using millimetre-sized ZIF-62 single crystals and centimetre-sized ZIF-62 glass, we demonstrate the scalability and processability of our materials. Further, following the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In contrast, Figure S14b shows that rescanning a glass originally prepared with a high water vapor pressure ( P max = 111.1 bar) in an Al crucible reveals a glass transition temperature of ∼277 °C (compared to ∼200 °C when performing a scan with water), followed by a weight loss (∼1 wt %, see Figure S14c ), which is likely due to water release as this has previously been found to be released around this temperature in the ZIF-62 crystal. 35 These measurements suggest a permanent densification effect inducing a T g drop of ∼45 °C (compared to T g ∼ 320 °C when making the ZIF-62 glass without water), while the presence of water vapor induces another T g drop of ∼70 °C. Notably, upon a subsequent upscan (after first scanning to 450 °C), the densification effect is relaxed, and we measure a T g of ∼320 °C ( Figure S14b ).…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, Figure S14b shows that rescanning a glass originally prepared with a high water vapor pressure ( P max = 111.1 bar) in an Al crucible reveals a glass transition temperature of ∼277 °C (compared to ∼200 °C when performing a scan with water), followed by a weight loss (∼1 wt %, see Figure S14c ), which is likely due to water release as this has previously been found to be released around this temperature in the ZIF-62 crystal. 35 These measurements suggest a permanent densification effect inducing a T g drop of ∼45 °C (compared to T g ∼ 320 °C when making the ZIF-62 glass without water), while the presence of water vapor induces another T g drop of ∼70 °C. Notably, upon a subsequent upscan (after first scanning to 450 °C), the densification effect is relaxed, and we measure a T g of ∼320 °C ( Figure S14b ).…”
Section: Resultsmentioning
confidence: 88%
“…136 Recently, Knebel et al have reported a synthetic approach to increase the CO 2 diffusion in ZIF-62 glass by controlling the melting and tempering parameters, resulting in changes of the pore channel structure in the ångström-range. 137 Another promising approach, still not applied in the synthesis of MOF glasses, is the use of small molecules such as carbonates, that decompose during the melting and tempering of the glass. This method has shown promise with introducing pores in inorganic glasses.…”
Section: Non-reversible High Temperature Phase Transitionsmentioning
confidence: 99%
“…The requirement to harness good processability for practical use has led to the study of microporous adsorbents that can change phases between liquid, glass, and crystal. 7 One typical example is the synthesis of molecularly networked liquids and glasses 8,9,10 from crystalline metal-organic frameworks (MOFs) that have porous three-dimensional structures made of metal nodes and organic ligands. The transition of MOFs from crystal to liquid or glass phase was achieved by the heat-or mechanical force-induced cleavage and rearrangement of their coordination bonds, similar to the phase transition of inorganic materials like silica glasses.…”
Section: Introductionmentioning
confidence: 99%